Histopathologic Characterization of Brain Tumour Related Epilepsy and Review of Pathogenic Mechanisms - Chaturvedi, Sujata; Pant, Ishita; Rawat, Kavita; Sarma, Pragyan (Annals of Pathology and Laboratory Medicine, 2025)
Background: Brain tumour related epilepsy (BTRE) may occur in 40% to 60% of brain tumours. Its incidence is highly dependent on the location and type of tumour. With the underlying molecular mechanisms getting unravelled, treatment strategies are being designed accordingly. This retrospective study was undertaken to profile the histopathology samples received in our department with the clinical diagnosis of brain tumour related epilepsy. Methods: A retrospective study of 193 brain tumour related epilepsy cases received over a period of last 10 years (2014-24) was done. Histopathology records were revisited and the details of tumour type and grade, location and demographic details were mapped and analysed. These findings have been presented and brief review of molecular mechanisms in brain tumour related epilepsy has also been incorporated where applicable. Results: Of the 193 seizure associated brain tumour cases, 182 (94.30%) comprised of primary central nervous system tumours and 11 (5.7%) comprised of tumours metastatic to the brain. In our series, maximum cases were found in young male adults within the age group of 21-40 yrs. Commonest location was intraparenchymal (frontal) and commonest tumour was adult type diffuse glioma. Conclusion: Collation of clinical, demographic and histopathology findings is necessary in brain tumour related epilepsy for identifying the common patterns and developing management strategies accordingly.